PENINGKATAN KEMAHIRAN BERBAHASA INDONESIA DALAM MENULIS ILMIAH MAHASISWA BIMBINGAN DAN KONSELING MELALUI COLLABORATIVE WRITING AND MULTIPLE DRAFTING - Murtono . (Universitas PGRI Semarang, 2014)
Abstract As one of the final goal of?é?á Indonesian learning, writing skill is the most complex skill if is it compared with the other three skills (listening, reading and speaking). Putting forward idea, thought, and point of view through written language is not easy work, especially for beginners. Therefore, it is needed certain ways (tips) to do it. This research of collaborative and multiple drafting learning model is chosen by the writer to enhance the Indonesian skill in making academic writing. It is a classroom action research. This research is done in some cycles, with evaluation for each cycle. From the result of these cycles. It is found out significant improvement of learning result, in term of either motivation in learning process, evaluation result of final cycle, or students?óÔé¼Ôäó attitude?é?á towards this model. From the result of observation, it is found out some data about seriousness, motivation, participation and activeness which show a very high level. It show an outstanding improvement of motivation. Additionally the result (achievement) of student?óÔé¼Ôäós Indonesian skill in making academic writing is very significantly improving in which in the preliminary stage, the grade is only 58, while in first cycle it gets improvement of grade of 74, and it also improves in the second cycle of 92 grade. The students?óÔé¼Ôäó response towards this mode is also good (positive). Key Words: language skill, collaborative writing and multiple drafting